Analysis of the most intense periods during elite soccer matches: effect of game location and playing position - Gualtieri, A.; Angonese, M.; Maddiotto, M.; Rampinini, E.; Ferrari Bravo, D.; Beato, M. (International Journal of Sports Physiology and Performance, 2025)
Purpose: This study aimed to quantify the game-speed demand of elite soccer players using time windows from 5 seconds to 10 minutes and to examine the effect of match location and playing position on game-speed outputs.